A Cross-Sectional Study of prevalence of Prostate lesions and inter-Observer Variability in Histopathological Reporting - Gulati, Rachna; Katoch, Neena; Dudani, Sharmila; Pandit, Subhendu; S Ahuja, Manish (Archives of Men's Health, 2021)
Introduction: To report the prevalence of various prostate lesions in the general population through cadaver prostates and to determine the interobserver variability for reporting high-grade lesions of the prostate. Materials and Methods: The cross-sectional study was carried out on 110 autopsy specimens of healthy prostate with deceased age over 40 years. The specimens were grossed, sectioned, stained and reported independently by the primary investigator resident and the senior professor. The lesions were categorized into prostatitis, benign prostate hypertrophy (BPH), prostate intraepithelial neoplasia (PIN) further graded as low grade (LGPIN) and high grade (HGPIN) and prostate cancer (PCa). Inter-rater kappa agreement was used to find the strength of agreement between the pathologists. Results: Among 110 prostate specimens, only 8(7.27%) cases had normal prostate with 72 (65.4%) having BPH and 12(10.9%) cases having prostatitis. There were 17 cases of PIN with 11 cases of HGPIN and 6 cases of LGPIN. Malignancy was seen in only a single case (95% Confidence Interval: 0% - 2.71%). The primary resident missed 4 cases of HGPIN and 2 cases of LGPIN. Interobserver agreement between the resident and senior pathologist was fair (Kappa 0.282, p value=0.335). Conclusion: In conclusion, prostate lesions remain latent and show high prevalence in general population without causing any symptoms. The study depicts a high interobserver variability of reporting the high-grade lesions of prostate since they cause a diagnostic dilemma with PCa. The consultation with uropathologists and use of molecular markers must be included in the diagnostic panel while reaching a final diagnosis.